Anagrus avalae Soyka, 1956, a new synonym of A. bakkendorfi Soyka, 1946 (Hymenoptera: Mymaridae) - Triapitsyn, Serguei V.; Baquero, Enrique; Rugman-Jones, Paul F. (Zootaxa, 2021)
Soyka (1946) described the European fairyfly species Anagrus bakkendorfi Soyka (Hymenoptera: Mymaridae) from a single female collected on the same day, 7.x.1931, together with several non-type specimens incorrectly labeled as paratypes (Chiappini & Triapitsyn 1999), on a window at its type locality, the former St. Ignatius Jesuit College in Valkenburg, Limburg, the Netherlands. Soyka (1956) did not mention type specimens of any of his species of Anagrus Haliday. He described Anagrus avalae Soyka (Soyka 1956) based apparently on a specimen collected on Mt. Avala, Belgrade, Serbia, former Yugoslavia, along with several other nominal species (some also from Valkenburg) that were later synonymized with A. avalae and A. bakkendorfi by Chiappini (1989) and Chiappini & Triapitsyn (1999). The only, minor, morphological difference between the two nominal species is the length of the ovipositor in females relative to the length of the protibia, being at least 2.6× in A. bakkendorfi and at most 2.3× in A. avalae (Triapitsyn 2015). Specimens identifiable as both species were captured by the second author in 2000 by a Malaise trap in Iratibizkar, Irati Forest (Selva de Irati), Navarra, Spain. Chiappini & Triapitsyn (1999) discussed both nominal species but despite recognizing their apparent conspecificity, no formal synonymy was proposed. Triapitsyn & Berezovskiy (2004) and Triapitsyn (2015) also did not propose synonymy because at that time genetic evidence for conspecificity was lacking. However, Triapitsyn et al. (2019) obtained DNA and sequenced selected mitochondrial and nuclear ribosomal gene regions (COI and ITS2) from a specimen unambiguously identified by the first author as A. avalae that was collected in Sevenoaks, Kent County, England, United Kingdom. Because of this we decided to collect fresh specimens identifiable as A. bakkendorfi for molecular analysis and genetic comparison with those identifiable as A. avalae. Based on the previous record (Triapitsyn 2015), several females of A. bakkendorfi were successfully captured by the second author on 4.ix.2020 in Irati Forest, preserved in ethanol, and shipped to the first and third authors for morphological and molecular identification, respectively.